A nomogram for predicting prognosis for young cervical neuroendocrine carcinoma: A SEER-based study and external validation - Xie, Ning; Yu, Haijuan; Lin, Jie; Deng, Sufang; Liu, Linying; Sun, Yang (Frontiers in Oncology, 2025)
BackgroundNeuroendocrine carcinoma of the cervix (NECC) is a rare and highly aggressive subtype of cervical carcinomas with poor prognosis. NECC tends to occur in young age which could severely impair mental and physical health of young patients. Therefore, this study aims to develop an individualized prognostic nomogram for young NECC patients.Methods360 young (≤45 years old) NECC patients were retrospectively selected from the Surveillance, Epidemiology and End Results (SEER) database and were randomly located to a training cohort and an internal validation cohort in a ratio of 7:3. Data from Fujian Cancer Hospital was used as an external validation cohort. Independent prognostic factors were identified by univariate and multivariate Cox regression analysis, and a prognostic nomogram for young NECC was developed. The predictive accuracy and clinical utility of the nomogram were assessed by area under the time-dependent receiver operating characteristic (timeROC) curve (AUC), the concordance index (C-index), calibration plots, and decision curve analysis (DCA). Finally, a simplified scoring system for clinical use was constructed by dividing patients into high-risk and low-risk groups.ResultsPathological type, FIGO stage, and surgery were independent risk factors by univariate and multivariate analysis (P < 0.05). The prognostic nomogram consisting of the above three independent risk factors had high accuracy. The AUC values of 5-year overall survival (OS) in the training, internal validation, and external validation cohorts were 0.805, 0.798 and 0.872, respectively. The prognostic nomogram also presented with good C-index and calibration plots. The DCA curve further confirmed that the nomogram had a high clinical net benefit. According to the median prognostic index (median PI=18.6), all patients were categorized into high-risk group and low-risk group. The 5-year OS of the high-risk NECC group was significantly worse than that of the low-risk group among three cohorts (P<0.05).ConclusionsPathological type, FIGO stage, and surgery were identified as independent prognostic risk factors for young NECC patients. Based on the nomogram, gynecologic oncologists can accurately and easily predict the prognosis of young NECC and provide scientific guidance for individualized treatment.